Energy‐Conserving Data Transfer in the Partitioned Treatment of Thermo‐Viscoplastic Problems. Issue 1 (December 2013) - Erbts, Patrick; Rothe, Steffen; Düster, Alexander; Hartmann, Stefan
Abstract Partitioned coupling approaches are a well‐established solution strategy for the numerical treatment of multi‐physical problems. The nature of the decoupled algorithm requires a repetitive data exchange to achieve a proper balance between the different fields concerned. In the case of non‐matching meshes, the data transfer becomes of particular importance when the values of interest are only available at the local integration points. In this case, an additional interpolation scheme has to be initialized in order to assure an energy‐conserving data transfer. This contribution looks at a thermo‐viscoplastic material that requires the interpolation of history‐dependent data onto the thermal mesh. We propose a technique employing a least‐square fit procedure and present a numerical example demonstrating the accurate data transfer. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)